Nidificación del Picaflor Esmeralda (Agyrtria versicolor) en el Parque Nacional Iguazú, Misiones, Argentina - Militello , Eduardo R.; Castillo, Rodrigo (Nuestras Aves, 2005)
Este artículo no cuenta con un resumen.